Kepemimpinan Transformasional dan Employee Engagement terhadap Kinerja Karyawan Hotel Plaza Manado - Wijaya, Kenneth D.; Pio, Riane J.; Tampi, Dolina L. (Productivity, 2020)
This study aims to determine the effect of Transformational Leadership and Employee Engagement on Employee Performance at Hotel Plaza Manado. This approach uses a quantitative approach, with a sample of 30 respondents. The results showed. Transformational Leadership has a positive and significant effect on Employee Engagement. Transformational Leadership has a significant and positive effect on employee performance. The results of this study also show that there is a positive and insignificant influence between Employee Engagement on Employee Performance.